Monsoon-driven seasonal dynamics of trace metal contamination and ecological risk in sediments of multiple ecosystems, Mandapam group of islands, Gulf of Mannar, India - Rakhil Dev; P. Hari Praved; Babu Nallusamy; Mohammed Noohu Nazeer; P. Sreeraj; Reji Srinivas; Anoop Krishnan; Karri Ramu; Chinmay Shah (Gondwana Research, 2026)

Cross-Sectional Survey of Physician-Reported Usage Patterns and GC–MS Phytochemical Profiling of Mahabala Tailam - Anoop A.K.; P. M. Varier; Ramesh P.R.; Haritha N.; Arjun M.K.; Deepak M.; Venugopalan P (Journal of Pharmaceutical Innovation, 2026)

Hydrogeochemical characterization, spatial distribution, and suitability of groundwater for drinking and irrigation in the Aravalli Range, Haryana, India - Manoj Kumar; Anoop Yadav; Manjeet Bansal; Vinod Kumar Garg; Pawan Kumar Rose; Ram Pravesh Kumar; Bhupendra P. Singh (Environmental Sustainability, 2026)

Spatio-temporal analysis of rainfall extremes and drought variability in the Tel basin, Odisha, India, under changing climate - Pushpanjali Kumari; H. P. Singh; Pankaj Dangi; Anoop Kumar Shukla (Innovative Infrastructure Solutions, 2026)
Climate change has significantly influenced temperature and rainfall patterns, disrupting hydrological cycles and increasing extreme weather events. This study analyses spatial and temporal variations in rainfall trends and extreme climatic indices in the Tel Basin, Odisha, India, from 1981 to 2021. Rainfall trends were assessed using the Mann–Kendall test and Sen’s slope estimator, while extreme climatic indices were evaluated using the Climpact tool. Drought variability was examined using the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI), accounting for the role of temperature in drought intensification. The results reveal pronounced spatial heterogeneity in rainfall trends. Monsoon rainfall shows increasing trends (up to 17.48 mm/decade), while pre-monsoon rainfall is declining (up to −2.64 mm/decade). Heavy rainfall events (R20mm, R30mm) are rising, whereas consecutive dry days (CDD) have increased by ~ 5 days/decade and consecutive wet days (CWD) have decreased by ~ 3 days/decade. Drought analysis shows that SPI-6 exhibits a weak increasing trend (Sen’s slope = 0.001), whereas SPEI-6 indicates a stronger drying pattern (Sen’s slope = − 0.005), highlighting the influence of rising temperatures. Temperature extremes, such as TXx (~ 0.02 °C year⁻ 1 ), along with an increase in tropical nights, indicate intensified warming, which enhances evapotranspiration and increases agricultural water stress. The results stress the urgent need for adaptive water resource management, climate-resilient agriculture, and improved irrigation planning in the Tel Basin to combat the growing climate-induced vulnerabilities.

Preliminary analysis and applications of the Indian Ocean wave drifter program - P. G. Remya; N. Suresh Kumar; Sundhar B. Mithun; B. Praveen Kumar; T. R. Anoop; Venkat Shesu Reddem; C. Jeyakumar; Aneesh A. Lotliker; E. Pattabhi Rama Rao; T. M. Balakrishnan Nair (Frontiers in Marine Science, 2025)
The Southern Ocean (SO) is a critical driver of global wave dynamics, generating long-period swells that propagate vast distances and significantly impact far distant coastal regions, including the Indian coastal regions. Climate change has intensified westerly winds and altered storm tracks in the Southern Hemisphere, resulting in higher wave heights and longer periods, which in turn increase the risk to coastal regions.​ However, the remote and harsh environment in the SO has historically limited in-situ wave observations, hindering a comprehensive understanding of the wave characteristics in the region. To bridge this gap, the Indian National Centre for Ocean Information Services (INCOIS) launched the Indian Ocean Wave Drifter (IOWD) program in 2021 under the Deep Ocean Mission to address the in-situ data gap in the Southern Indian Ocean. Through the deployment of GPS-enabled directional wave spectra drifters, the program has enabled near-real-time observations of wave characteristics across the SO. This article highlights the early outcomes of the IOWD program, including wave model validation, Stokes drift estimation, and swell tracking. The study emphasizes the importance of sustained in-situ observations from remote oceans for improving wave forecasting, enhancing coastal preparedness, and advancing scientific understanding of wave–current interactions and climate variability in the Indian Ocean region.

Youngest Toba Tuff (YTT) beds as a Late Pleistocene isochron in the Indian subcontinent? New geochronological and sedimentological insights - Devara Anil; Monika Devi; Prabhin Sukumaran; B. V. Lakshmi; K. Deenadayalan; Sunil Kumar; Ambili Anoop; Zakir Khan; Vrushab Mahesh; Gopesh Jha; P. Ajithprasad; Naveen Chauhan (Journal of Quaternary Science, 2025)
The ~75 ka Young Toba super‐eruption was a catastrophic extreme event that spewed vast quantities of volcanic ash and aerosols and is argued to have caused a drastic volcanic winter, climatic upheaval, and a human genetic bottleneck. The global and regional impacts of the eruption on climate dynamics and past hominin populations are strongly contested due to conflicting global climatic records and archeological datasets. The Indian subcontinent is a key place for Toba research due to its proximity to Mt. Toba (Indonesia). Most of central and peninsular India is estimated to have been covered by a ~5 cm ash layer, with deposits found in different fluvial systems across the subcontinent. For a long time, many of these Youngest Toba Tuff (YTT) deposits, occurring in both archeological and non‐archeological contexts, were believed to be primary tephra deposits dating to ~75 ka. However, the use of YTT as a Late Pleistocene chronological marker is surrounded by many uncertainties, primarily due to the complex and varying nature of the depositional and sedimentary contexts of YTT and chronological irregularities. Recent sedimentological and geochronological data indicate that most of the YTT deposits in India are secondary deposits, resulting from later erosion and redeposition occurring thousands of years after the eruption. This highlights the unreliability of YTT as an isochron and raises questions about the credibility of paleoclimate (terrestrial and marine) and archeological datasets that use YTT as a chronological marker. Our study contributes to this debate and reveals the complex redepositional history of YTT deposits in the Indian subcontinent through geochronological and geoarchaeological analyses of YTT‐bearing sequences from Motravulapadu, Andhra Pradesh, India. Our findings suggest that the final burial of YTT occurred around 30 ka, highlighting a temporal gap of more than 40 000 years after the eruption. Notably, the redeposited tephra horizon appears visually uniform and compositionally pure, despite its secondary context, adding complexity to its stratigraphic interpretation. Our multiproxy sedimentological approach demonstrates the importance of integrating detailed stratigraphic, magnetic, granulometric, and chronological analyses to resolve such depositional ambiguities; it underscores the need for similar frameworks in future studies of YTT‐bearing sequences. We suggest that YTT in India cannot be used as a reliable chronological marker without independent age estimations of its deposition. However, it has significant potential for identifying regional geological events.

Bioactive human platelet lysate gel for enhanced proliferation of human umbilical cord tissue derived mesenchymal stem cells - Seetha S. Babu; M. Kamaraj; T. G. Nithya; P. Raghu Babu; Gayathri Anoop (Cell and Tissue Banking, 2025)

Thunderstorm prediction over Eastern state of India during pre-monsoon season in 2018 using artificial neural network model - Nagaraju Vanganuru; P. Sardar Maran; L. Lakshmanan; Anoop Kumar Mishra; Araveti Sandeep (Theoretical and Applied Climatology, 2025)

Microstructures along the Indian west-coast continental shelf: layering and vertical mixing - Mayur Gachake; Anoop A. Nayak; P. Amol; P.N. Vinayachandran (Continental Shelf Research, 2025)

Seaweed assisted preparation of Fe2O3 nanoparticles and their antiviral studies against White Spot Syndrome Virus (WSSV): In vitro and in silico approach. - R. Namitha; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; P. Santhiya; I.S. Bright Singh; G. Dharani; K. Govindaraju (Aquaculture, 2024)

Neck extensor myopathy- a treatable cause of dropped head syndrome - Nibu Varghese; Vimal Chandraghosh K D; Deepak Menon; Abdurahiman P; Anoop Kattadimmal; Jubin Mathew; Shobika B S; Nyla Mary Babu (Acta Neurologica Belgica, 2024)

Differences in iodine chemistry over the Antarctic continent - Anoop S. Mahajan; Shrutika Wagh; Rafael P. Fernandez; Surendra Singh; Silvia Bucci; Alfonso Saiz-Lopez (Polar Science, 2024)

Thermo-economics, emissions, and sustainability comparison of a novel hybrid evaporative cooled solid oxide fuel cell-recuperated gas turbine with conventional system - Abhinav Anand Sinha; Tushar Choudhary; Anoop Kumar Shukla; P. Ahmadi (Process Safety and Environmental Protection, 2024)

Synthesis and characterization of gold nanoparticles using Brevibacterium casei (SOSIST-06) isolated from Southern Ocean water samples and their in vitro and in silico anti-WSSV activity - R. Namitha; B. Abirami; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; K. Manigundan; M. Radhakrishnan; P. Santhiya; Parli V. Bhaskar; K. Govindaraju; I.S. Bright Singh; G. Dharani (Aquaculture, 2024)

Year-long ground-based observations of bromine oxide over Bharati Station, Antarctica - Shrutika P. Wagh; Sankirna D. Joge; Surendra Singh; Prithviraj Mali; Steffen Beirle; Thomas Wagner; Silvia Bucci; Alfonso Saiz-Lopez; Rohini Bhawar; Anoop S. Mahajan (Polar Science, 2023)

Unravelling submarine channel morphology in the lower Bengal Fan through ultra-high-resolution autonomous underwater vehicle (AUV) survey - C. M. Bijesh; S. Vadakkepuliyambatta; J. John Savio; S. Ramesh; N. R. Ramesh; T. R. Anoop; P. Kunnummal; R. Ramesh; P. John Kurian; G. A. Ramadass (Geo-Marine Letters, 2023)

Pattern and drivers of danaine butterfly migration in Southern India: implications for conservation - P. A. Vinayan; M. A. Yathumon; N. S. Sujin; B. N. Anjan Kumar; P. A. Ajayan; P. K. Muneer; N. M. Vishnu; C. S. Anwar; N. R. Anoop (Journal of Insect Conservation, 2023)

Efficacious slosh suppression technique in road tankers to enhance the effectiveness of drinking water distribution - Unnikrishnan G; Anoop F. R; Abhilash Suryan; Pramoj Sanker P S (Chemosphere, 2023)

Turbulent dissipation rates across the Summer Monsoon Current - Anoop A. Nayak; Vinayachandran P. N.; Jenson V. George (Ocean Dynamics, 2022)

Lipid-Based Vesicles: a Non-invasive Tool for Transdermal Drug Delivery - Alan Raj; Sarath Chandran C.; Anoop Narayanan V.; Aparna Ivon; Nazeera Farzana N. M.; Neethu Narayan P. P. (Journal of Pharmaceutical Innovation, 2022)

Retrieval of Broadband Optical Properties from Ambient Aerosols Measurements Using Inverse Mie Calculations - Aiswarya Saseendran; Shebin John; Anoop Pakkattil; Arun P. Thomas; Sushmitha Adiga; Jun Chen; Claudio Mazzoleni; Deepa Viswanath; Ravi Varma (Aerosol Science and Engineering, 2022)

An environmental green approach for the effective removal of malachite green from estuarine waters using Pistacia vera L. shell-based active carbon - Harsha Mahadevan; P. V. M. Nimina; K. Anoop Krishnan (Sustainable Water Resources Management, 2022)

Atmospheric Aerosol Scattering Coefficients in a Broad Visible Spectral Region - R. Arun; P. Anoop; S. John; J. Chen; V. Deepa; R. Varma (Aerosol Science and Engineering, 2021)

Spring-neap tides influence on bioavailability of metals and bioaccumulation in edible biota of the Zuari (tropical) Estuary - Maheshwar R. Nasnodkar; Ganapati N. Nayak; Priyanka P. Bhangle; Anoop Kumar Tiwari (Environmental Monitoring and Assessment, 2021)

Surface Inorganic Iodine Speciation in the Indian and Southern Oceans From 12°N to 70°S - Rosie Chance; Liselotte Tinel; Amit Sarkar; Alok K. Sinha; Anoop S. Mahajan; Racheal Chacko; P. Sabu; Rajdeep Roy; Tim D. Jickells; David P. Stevens; Martin Wadley; Lucy J. Carpenter (Frontiers in Marine Science, 2020)

Lectotypification of five names in Indian Tephrosia (Fabaceae) - Anoop P. Balan; R. Prakashkumar (Kew Bulletin, 2020)

Plasma Biomarkers of Inflammation Reflect Seizures and Hemorrhagic Activity of Cerebral Cavernous Malformations - Romuald Girard; Hussein A. Zeineddine; Maged D. Fam; Anoop Mayampurath; Ying Cao; Changbin Shi; Robert Shenkar; Sean P. Polster; Michael Jesselson; Ryan Duggan; Abdul-Ghani Mikati; Gregory Christoforidis; et al. (Translational Stroke Research, 2018)

Gut microbiome contributes to impairment of immunity in pulmonary tuberculosis patients by alteration of butyrate and propionate producers - Abhijit Maji; Richa Misra; Darshan B. Dhakan; Vipin Gupta; Nitish K. Mahato; Rituja Saxena; Parul Mittal; Nitin Thukral; Eshan Sharma; Anoop Singh; Richa Virmani; Mohita Gaur; et al. (Environmental Microbiology, 2018)
Summary Tuberculosis (TB) is primarily associated with decline in immune health status. As gut microbiome (GM) is implicated in the regulation of host immunity and metabolism, here we investigate GM alteration in TB patients by 16S rRNA gene and whole‐genome shotgun sequencing. The study group constituted of patients with pulmonary TB and their healthy household contacts as controls (HCs). Significant alteration of microbial taxonomic and functional capacity was observed in patients with active TB as compared to the HCs. We observed that Prevotella and Bifidobacterium abundance were associated with HCs, whereas butyrate and propionate‐producing bacteria like Faecalibacterium , Roseburia , Eubacterium and Phascolarctobacterium were significantly enriched in TB patients. Functional analysis showed reduced biosynthesis of vitamins and amino acids in favour of enriched metabolism of butyrate and propionate in TB subjects. The TB subjects were also investigated during the course of treatment, to analyse the variation of GM. Although perturbation in microbial composition was still evident after a month's administration of anti‐TB drugs, significant changes were observed in metagenome gene pool that pointed towards recovery in functional capacity. Therefore, the findings from this pilot study suggest that microbial dysbiosis may contribute to pathophysiology of TB by enhancing the anti‐inflammatory milieu in the host.

The complete mitochondrial genome of Euphlyctis karaavali (Amphibia: Anura) with a note on its range expansion - V. S. Anoop; Kiran S. Kumar; K. C. Sivakumar; Dinesh Reghunathan; P. Manoj; Kaushik Deuti; Sanil George (Conservation Genetics Resources, 2017)

Indian Ocean Dipole modulated wave climate of eastern Arabian Sea - T. R. Anoop; V. Sanil Kumar; P. R. Shanas; J. Glejin; M. M. Amrutha (Ocean Science, 2016)
Intrinsic modes of variability have a significant role in driving the climatic oscillations in the oceanic processes. In this paper, we investigate the influence of an inter-annual mode of variability, the Indian Ocean Dipole (IOD), on the wave climate of the eastern Arabian Sea (AS). Using measured, modeled and reanalysis wave data and reanalysis wind data, we show that the IOD plays a major role in the variability of wave climate of the study region. Due to the IOD-induced changes in equatorial sea surface temperature and sea level pressure, the winds from the northern AS gets modified and cause inter-annual variability in the wave climate over the eastern AS. The changes in wind field over the AS due to the IOD influence the generation or dissipation of the wave field and hence cause a decrease in northwest short-period waves during positive IOD and an increase during negative IOD.

P alaeoenvironmental implications of evaporative gaylussite crystals from Lonar Lake, central India - A. ANOOP; S. PRASAD; B. PLESSEN; N. BASAVAIAH; B. GAYE; R. NAUMANN; P. MENZEL; S. WEISE; A. BRAUER (Journal of Quaternary Science, 2013)
We have undertaken petrographic, mineralogical, geochemical and isotopic investigations on carbonate minerals found within a 10‐m‐long core from Lonar Lake, central India, with the aim of evaluating their potential as palaeoenvironmental proxies. The core encompasses the entire Holocene and is the first well‐dated high‐resolution record from central India. While calcite and/or aragonite were found throughout the core, the mineral gaylussite was found only in two specific intervals (4630–3890 and 2040–560 cal a BP). Hydrochemical and isotope data from inflowing streams and lake waters indicate that evaporitic processes play a dominant role in the precipitation of carbonates within this lake. Isotopic (δ 18 O and δ 13 C) studies on the evaporative gaylussite crystals and residual bulk carbonates (calcite) from the long core show that evaporation is the major control on δ 18 O enrichment in both the minerals. However, in case of δ 13 C additional mechanisms, for example methanogenesis (gaylussite) and phytoplankton productivity (calcium carbonate), play an additional important role in some intervals. We also discuss the relevance of our investigation for palaeoclimate reconstruction and late Holocene monsoon variability. Copyright © 2013 John Wiley & Sons, Ltd.

Provenance variation in wood anatomical properties of selected acacia species - E. V. Anoop; V. Ajayghosh; P. Muhammed Shabab; P. Aruna (Journal of the Indian Academy of Wood Science, 2012)

Inter-clonal variation in wood properties of selected clones of Eucalyptus camaldulensis Dehnh. - E. V. Anoop; D. Rajasugunasekar; P. Neetha; V. Ajayghosh; P. Aruna (Journal of the Indian Academy of Wood Science, 2012)

Anatomical variation in the juvenile wood of Acacias grown in the South Indian state of Kerala - R. V. Rao; E. V. Anoop; V. V. Sheena; P. Aruna; V. Ajayghosh (Journal of the Indian Academy of Wood Science, 2011)

Processing and utilization of coconut wood in Kerala - E. V. Anoop; V. V. Sheena; P. Aruna; V. Ajayghosh (Journal of the Indian Academy of Wood Science, 2011)

Provenance variation in wood chemical properties of Acacia mangium willd. and Acacia auriculiformis cunn., grown in a wet humid site in Thrissur district of Kerala, South India - K. M. Mohammed Raphy; E. V. Anoop; P. Aruna; V. V. Sheena; V. Ajayghosh (Journal of the Indian Academy of Wood Science, 2011)

Variation in wood anatomical properties of selected indigenous, multipurpose tree species grown in research trials at LRS Thiruvazhamkunnu, Palakkad, Kerala - E. V. Anoop; V. Ajayghosh; Hariharan Pillai; Sumesh Soman; V. V. Sheena; P. Aruna (Journal of the Indian Academy of Wood Science, 2011)

In vitro direct shoot regeneration from proximal, middle and distal segment of Coleus forskohlii leaf explants - Gaurav Krishna; P. Sairam Reddy; N. Anoop Nair; P. W. Ramteke; P. S. Bhattacharya (Physiology and Molecular Biology of Plants, 2010)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Removal of Atrazine from Water by Low Cost Adsorbents Derived from Agricultural and Industrial Wastes - Rajendra Kumar Sharma; Anoop Kumar; P. E. Joseph (Bulletin of Environmental Contamination and Toxicology, 2008)

Apolipoprotein E polymorphism in Northern Indian patients with coronary heart disease: Phenotype distribution and relation to serum lipids and lipoproteins - Kalpana Luthra; Balram Bharghav; Shivani Chabbra; Nibhriti Das; Anoop Misra; Dharam P. Agarwal; Ravindra M. Pandey; L.M. Srivastava (Molecular and Cellular Biochemistry, 2002)

Picroliv - a natural product protects cells and regulates the gene expression during hypoxia/reoxygenation - Jaya P. Gaddipati; Subhashree Madhavan; Gurmel S. Sidhu; Anoop K. Singh; Pankaj Seth; Radha K. Maheshwaril (Molecular and Cellular Biochemistry, 1999)